043 A specialist cognitive clinic for the deaf community. Issue 12 (14th November 2019) - Harris, Matthew; Au, Darica; Judd, Katy; Atkinson, Joanna; Mummery, Catherine
Abstract : Background: Early dementia diagnosis is crucial to ensure timely treatment and support. Approximately 100, 000 people in the UK are Deaf and use British Sign Language as their first language. For this population access to healthcare can be difficult, clinical assessment challenging and misdiagnosis may occur. In August 2011, a specialist cognitive clinic for the Deaf community was established at the National Hospital for Neurology and Neurosurgery. We sought to evaluate this service to inform future provision of care. Methods: We retrospectively analysed electronic patient records from August 2011 until December 2018. Results: 36 patients were reviewed aged 35–83 years (median 71.5). 83% of those referred did not have a prior diagnosis. 17% had previously been given a provisional diagnosis, however this was changed in 67% of cases following review in our clinic. All patients underwent neuropsychological assessment and in 92% cranial imaging was performed. 8% additionally underwent FDG-PET and 25% lumbar puncture. 47% were diagnosed with a neurodegenerative disorder (Alzheimer's Disease in 77%), 6% mild cognitive impairment, 11% a pre-existing neurological disorder and 19% with subjective memory complaints without evidence of neurodegeneration. Donepezil was commenced in all patients diagnosed with Alzheimer's disease. 9% experienced adverse effects and changed medication. Conclusion: In this evaluation, we found that Deaf patients had difficulties obtaining an accurate diagnosis prior to clinic and we observed a high proportion of neurodegenerative and neurological diagnoses (64%) compared to other cognitive clinics (reportedly 40–50%). We believe these results highlight the challenges Deaf patients have in accessing healthcare and this underscores the importance of this service in ensuring patients receive an accurate and timely diagnosis.